A Multicenter Phase II Trial of Docetaxel, Cisplatin, and Cetuximab (TPEx) Followed by Cetuximab and Concurrent Radiotherapy for Patients With Local Advanced Squamous Cell Carcinoma of the Head and Neck (CSPOR HN01: ECRIPS Study) - Zenda, Sadamoto; Ota, Yosuke; Kiyota, Naomi; Okano, Susumu; Fujii, Masato; Kitamura, Morimasa; Takahashi, Shunji; Ueda, Tsutomu; Monden, Nobuya; Yamanaka, Takeharu; Tahara, Makoto (Frontiers in Oncology, 2019)
Background Induction chemotherapy (IC) is a treatment option for locally advanced squamous cell carcinoma of the head and neck (LA SCCHN). However, treatment with docetaxel, cisplatin, and 5-FU (TPF) followed by cisplatin and radiotherapy is controversial because of toxicity concerns. The aim of this phase II study was to assess the feasibility of docetaxel, cisplatin, and cetuximab (TPEx) followed by cetuximab and concurrent radiotherapy for LA SCCHN. Patients and methods We enrolled patients with histological evidence of squamous cell carcinoma of the oropharynx, hypopharynx, or larynx without distant metastases. IC comprised cisplatin (75 mg/m2) and docetaxel (75 mg/m2) on day 1, repeated every 3 weeks for up to three courses. Cetuximab was initiated at 400 mg/m2, followed by 250 mg/m2 doses weekly until the end of radiotherapy. Radiotherapy (70 Gy/35 fr/7 w) was initiated after the last docetaxel administration. The primary endpoint was the rate of treatment completion. Results We enrolled 54 patients (median age, 58 years) between August 2013 and October 2015. Our patients were 49 males and 5 females with hypopharyngeal (n = 28), oropharyngeal (n = 19), or laryngeal (n = 7) cancers, and 48 of them had stage IV disease. The overall response rate was 72.2% with a median follow-up of 36.1 months and a 3-year overall survival of 90.7%. The treatment completion rate was 76%; 50 patients (93%) received ≥2 courses of IC, and 41 (76%) completed radiotherapy. The frequencies of grade ≥3 febrile neutropenia or allergy/infusion reactions were 39% and 11%, respectively. There was one treatment-related death. Conclusions IC with TPEx followed by cetuximab with concurrent radiotherapy showed acceptable compliance for the treatment of LA SCCHN. However, high frequency of febrile neutropenia remains a challenge and further improvement in the management of TPEx is necessary. Trial registration UMIN000009928